Lock-out, lock-in, and networked sovereignty. Resistance and experimentation in Africa’s trajectory towards AI - Iginio Gagliardone (Liinc em Revista)
The conception of digital sovereignty has been associated, especially in the early stages of the diffusion of the Internet, with efforts to keep specific data and information outside of a state’s jurisdiction. AI sovereignty responds to an almost opposite logic, indicating the ability of a state to access and make use of data that are produced within its jurisdiction. These two strategies –which I refer to as lock-out and lock-in sovereignty –share some common roots (e.g. the attempt to protect and enhance specific cultural attributes recognised as important by a national community), but they also point to different technical, economic, and political characteristics needed to enforce one or the other type of sovereignty. The article examines key elements that set these concepts, and their implementation, apart and how they intersect with both existing and potential articulations of national sovereignty in Africa. In particular it opposes a negative –and still pervasive –definition of sovereigntyapplied to African states, based on the Westphalian ideal and “measuring the gap between what Africa is and what we are told it ought to be” (Mbembe 2019, p.26); and the possibilities disclosed by re-appropriating practices of “networked sovereignty” (Mbembe, 2016).